KEMAMPUAN ANALISIS GRAFIK FUNGSI KUADRAT TERINTEGRASI NILAI-NILAI KEISLAMAN - Erna Sari Agusta (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2023)
Abstract This study aims to determine students' analytical abilities in the matter of quadratic function graphs as well as learn the learning of quadratic function graphs integrated with Islamic values at MTsN 28 Jakarta. This Classroom Action Research was conducted in 2 cycles on Quadratic Function Graph material. Each process consists of planning, implementing, observing, and reflecting. Through research, qualitative data on mathematics learning integrated with Islamic values were collected using observation techniques, interviews, field notes, and quantitative data analysis ability test results. Qualitative data was processed using a four-step qualitative analysis method: data collection, data reduction, data presentation, and conclusion, while the quantitative data were processed using descriptive statistics. The results showed that the student's analytical abilities on the quadratic function graph material integrated with Islamic values developed well. An analogy between the effects of the x2 coefficient, x coefficient, and constant values on the shape of the graph teaches the material for graphing quadratic functions integrated with Islamic values. Islamic values that appear based on students' analytical abilities on changes in the form of the quadratic function graph are the concepts of faith, lust (desire), and charity (deeds). After learning the quadratic function graph integrated with Islamic values, the measurement results increased the analytical ability score from the average value and the percentage of student learning completeness. With the results of this study, it is recommended that mathematics learning is integrated with Islamic values as a learning approach that can improve students' mathematical analysis abilities.   Abstrak Penelitian ini bertujuan untuk mengetahui kemampuan analisis siswa pada materi grafik fungsi kuadrat sekaligus mengetahuipembelajaran grafik fungsi kuadrat yang terintegrasi nilai-nilai keislaman di MTsN 28 Jakarta. Penelitian Tindakan Kelas ini dilakukan sebanyak dua siklus pada materi Grafik Fungsi Kuadrat. Setiap siklus terdiri dari tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Melalui penelitian dikumpulkan data kualitatif mengenai pembelajaran matematika yang terintegrasi nilai-nilai keislaman menggunakan teknik observasi, wawancara dan catatan lapangan; dan data kuantitatif hasil tes kemampuan analisis. Data kualitatif diolah menggunakan metode analisis kualitatif empat langkah yaitu pengumpulan data, reduksi data, penyajian data dan penyimpulan; sedangkan data kuantitatif diolah menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa kemampuan analisis siswa pada materi grafik fungsi kuadrat yang terintegrasi nilai-nilai keislaman berkembang dengan baik. Materi grafik fungsi kuadrat yang terintegrasi dengan nilai-nilai keislaman dibelajarkan dengan menganalogikan antara pengaruh koefisien x2, koefisien x, dan nilai konstanta terhadap bentuk grafik. Nilai-nilai keislaman yang muncul berdasarkan kemampuan analisis siswa pada perubahan bentuk grafik fungsi kuadrat adalah konsep iman, nafsu (keinginan), dan amal (perbuatan). Hasil pengukuran setelah dilakukan pembelajaran grafik fungsi kuadrat yang terintegrasi nilai-nilai keislaman diperoleh peningkatan skor kemampuan analisis dari nilai rata-rata  dan prosentase ketuntasan belajar siswa. Dengan peningkatan nilai rata-rata dan persentase ketuntasan belajar direkomendasikan pembelajaran matematika terintegrasi nilai-nilai keislaman sebagai suatu pendekatan pembelajaran yang dapat meningkatkan kemampuan analisis matematis siswa.